Indian Legal Framework on the Right to Privacy in Cyberspace-Issues and Challenges - Manjula Raghav; Sanjana Sharma Marwaha (Fiat Justisia: Jurnal Ilmu Hukum, 2023)
Right to privacy is nowhere cited in the Constitution of India in any specific and express words. However, this right is culled from Article 21 read with Directive Principle of State Policy by the judiciary. It is to be noted that like other fundamental rights, right to privacy is not an absolute right. Privacy is not just confined to some specific place or domain.  But recent developments in technology and internet usage has rapidly exposed privacy to potential threats. On the one hand, technology has provided endless possibility to human beings of development but on the other hand, it has posed numerous challenges in front of us.  Unreasonable interference upon person’s domain, disclosure of personal information, misappropriation of some one’s identity, hacking, digital stalking etc. will lead to violation of privacy. The present paper discusses the relationship between privacy and the increasing usage of technology. In this regard, protection provided by Indian laws as well as international instruments will be discussed to protect privacy right in digital world. After discussing issues and challenges, viable solutions will be discussed at the end of the article.